San Sevaka Dharma dalam Naskah Aji Sarasoti Merapi-Merbabu - Anak Agung Gde Alit Geria; I Gde Agus Darma Putra (Jurnal Kajian Bali (Journal of Bali Studies), 2023)
Sevaka Dharma means servant of truth. This phrase only occurs in the Aji Sarasoti Merapi-Merbabu (MM) manuscript. This paper aims to elaborate on the phrase sa? sevaka dharma (a person who is honored for serving the truth) which is mentioned in the first line of the text so that the concept of sa? sevaka dharma can be understood correctly. Aji Sarasoti text which is used as the material object in this paper is the Merapi-Merbabu manuscript, which is stored in the National Library of Indonesia, code PNRI 11 L. 254. The method used is the basic method, while the theory used is hermeneutic. The PNRI 11 L. 254 manuscript contains not only the Aji Sarasoti text but also the Aji Panarawangan and Aji Pangsoluan Raga. Likewise, other Aji Sarasoti manuscripts were published together with other texts in one file. Meanwhile, the Sa? Sevaka Dharma which is mentioned in the Aji Sarasoti text refers to someone who is having to understand the teachings. The teaching in question is the teaching of liberating knowledge (jñ?na).